L’égalité dans l’enseignement supérieur entre utopie et solutions concrètes - Dominique Bucheton; Jean-Marie De Ketele; Philippe Meirieu; Richard Etienne (Éducation et Socialisation)
The interventions of three specialists in pedagogy, university pedagogy and didactics established that other mechanisms than those of fractional distillation are possible and effective in higher education. The social and academic origins of students require them to meet the demands and customs of the academic world. Writing plays an essential part in success at this level and the organization of writing practice with tools and a progressive method constitutes somewhat of an innovation on which teacher-researchers can discuss. Higher education does not keep its promises of success because it systematically transforms its objectives into a prerequisite. However, the educational and didactic system is at least as important as the content of the training. Developing higher education in this direction is a political challenge which does not only focus on an elite, the "winners" only, to use the image of François Dubet.